MenuForside/BlogadenTeksterUfnetMusikNoerderierSozialOm

Sumfølger : Geometrisk serie - Nørderier/Teori

Geometrisk sumfølge er givet som: $$\sum_{k=0}^{n}{x^k} = \frac{x^{n+1} - 1}{x - 1}$$ Hvor \(x \neq 1\).

Bevis

Induktionsstart

Induktionsskridt

Lad $$\sum_{k=0}^{n}{x^k} = \frac{x^{n+1} - 1}{x - 1}$$ Vi får $$\sum_{k=0}^{n}{x^k} + x^{n + 1} =$$ $$\frac{x^{n+1} - 1}{x - 1} + x^{n + 1} =$$ $$\frac{x^{n+1} - 1 + (x - 1) x^{n+1}}{x - 1} =$$ $$\frac{x^{n+1} - 1 + x^{n+2} - x^{n+1}}{x - 1} =$$ $$\frac{x^{n+2} - 1}{x - 1}$$

Og vi har vist hvad vi skulle.